2015
DOI: 10.3390/ijms16059612
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Depletion Predicts the Prognosis of Patients with Hepatocellular Carcinoma Treated with Sorafenib

Abstract: The aim of this study was to determine whether skeletal muscle depletion predicts the prognosis of patients with hepatocellular carcinoma (HCC) that is being treated with sorafenib. We evaluated 40 consecutive HCC patients who received sorafenib treatment. The skeletal muscle cross-sectional area was measured by computed tomography at the third lumbar vertebra (L3), from which the L3 skeletal muscle index (L3 SMI) was obtained. The factors contributing to overall survival, sorafenib dose reduction, and discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 41 publications
8
77
0
Order By: Relevance
“…This result indicated that these malnutritional factors were important for the survival of patients with HCC treated with sorafenib. Several recent reports indicated that decreased skeletal muscle mass was an important prognostic factor in patients with chronic liver disease and HCC (2,3,5,6). These results suggested that preventing reductions in skeletal muscle thickness may improve the OS of patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This result indicated that these malnutritional factors were important for the survival of patients with HCC treated with sorafenib. Several recent reports indicated that decreased skeletal muscle mass was an important prognostic factor in patients with chronic liver disease and HCC (2,3,5,6). These results suggested that preventing reductions in skeletal muscle thickness may improve the OS of patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, an increasing number of studies have demonstrated that sarcopenia may affect the clinical state of patients with liver disease (1)(2)(3). Moreover, skeletal muscle wasting assessed by CT has been reported to be a prognostic marker for patients with hepatocellular carcinoma (HCC) treated with sorafenib (5,6). In those reports, skeletal muscle mass was usually measured by imaging modalities, such as CT and magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the duration of sorafenib treatment is significantly shorter in patients with LSMM than in non‐LSMM patients . In contrast, others did not investigate the therapy duration . These findings indicate that patients with LSMM are more likely to have a shorter duration of sorafenib treatment than non‐LSMM patients; however, previous studies have indicated that LSMM was associated with survival without analyzing the duration of sorafenib treatment with Cox regression analysis.…”
Section: Discussionmentioning
confidence: 84%
“…Body mass index (BMI) is usually used as a simple index of obesity that can be easily calculated using a patient's height and weight; however, body composition such as skeletal muscle mass and adipose tissue mass is not exactly reflected by BMI. In terms of prognosis, the effects of BMI are controversial in patients with HCC receiving sorafenib treatment . Sarcopenia, which is defined as both loss of skeletal muscle mass and function, is classified as primary sarcopenia (age‐related) and secondary sarcopenia (activity‐, disease‐, or nutrition‐related) by the European Working Group on Sarcopenia in Older People (EWGSOP) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation